Beispiel Nr: 02
$\text{Gegeben:}\\ \text{Bruch1:}\frac{a}{b} \\ \text{Bruch2:}\frac{c}{d} \\ \\ \text{Gesucht:} \\\text{Summe,Differenz,Produkt,Quotient} \\ \frac{a}{b} - \frac{c}{d}\\ \textbf{Gegeben:} \\ a=3 \qquad b=4 \qquad c=5 \qquad d=9\\ \\ \textbf{Rechnung:} \\ \text{Hauptnenner: kgV( }4,9 \text{) }= 36 \\ \text{Erweiterungsfaktoren: }\frac{36}{4}=9 \qquad \frac{36}{9}=4 \\ \\\text{Summe}\\ \frac{3}{4}+\frac{5}{9}=\frac{3\cdot9}{4\cdot9}+\frac{5\cdot4}{9\cdot4}= \frac{27+20}{36}=\frac{47}{36}=1\frac{11}{36} \\ \\\text{Differenz}\\ \frac{3}{4}-\frac{5}{9}=\frac{3\cdot9}{4\cdot9}-\frac{5\cdot4}{9\cdot4}= \frac{27-20}{36}=\frac{7}{36}=\frac{7}{36} \\ \\\text{Produkt} \\ \frac{3}{4} \cdot \frac{5}{9}=\frac{3\cdot5}{4\cdot9}= \frac{15}{36}=\frac{5}{12} \\ \\\text{Quotient} \\ \frac{3}{4} : \frac{5}{9}=\frac{3}{4} \cdot \frac{9}{5}= \frac{27}{20}=1\frac{7}{20} \\ $